INSTAGRAM-BASED PROMOTIONAL MODEL FOR PENDOWOREJO TOURISM VILLAGE YOGYAKARTA PROVINCE : Model Promosi Berbasis Instagram untuk Desa Wisata Pendoworejo, Provinsi Yogyakarta - Rahayu, Kania Sofiantina; Rana Wardah; Natasha Indah Rahmani; Helianthi Dewi; Rini Untari; Teguh Jati Purnama (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop an Instagram-based digital promotion model for Pendoworejo Tourism Village, Yogyakarta Province, in order to strengthen destination branding and improve the effectiveness of tourism marketing communication. The primary issues identified include the absence of a structured digital promotion system, inconsistent posting frequency, weak visual identity, and limited audience engagement on the official Instagram account of the tourism village. A mixed-methods approach was employed using the Design Thinking framework, consisting of the stages of empathize, define, ideate, prototype, and test. Data were collected through observation, in-depth interviews, questionnaires administered to 34 tourists, and documentation of the existing Instagram account. The findings reveal that tourists’ evaluations of content quality, visual design, captions, hashtags, engagement, and posting consistency were predominantly categorised as low to very low. During the ideation stage, an integrated promotional model was formulated, comprising strategies for informative, educational, promotional, and entertaining content; the development of a coherent visual identity based on colour schemes, typography, and communication tone; the optimisation of Instagram features such as reels, stories, and hashtags; and the preparation of a structured content calendar. The prototype stage produced an Instagram feed design and Story templates that more effectively represented the village’s natural and cultural attractions. Results from the limited testing phase indicate that the proposed model was perceived as easy to understand, practical to implement, and supportive of more systematic promotional management. This study concludes that an Instagram-based promotion model developed through the Design Thinking approach is effective in strengthening the branding of tourism villages and may serve as a reference for digital promotion strategies in similar destinations. The contribution of this research lies in the formulation of a structured, contextual, and user-centred digital promotion model for tourism villages.